Indoor Positioning System (IPS) for Guiding the Location Inventory Goods in Buildings - Widartono, Barandi Sapta (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Now is the spatial era, where position plays a role in providing information about the existence of objects on earth. Utilization of a variety of devices requires demands on location automation that are fast and accurate. Positioning technology, known as Location-Based Services (LBS), is highly dependent on the Global Satellite Satellite System (GNSS). Now for automatic positioning also started using the Indoors Positioning System (IPS), where GNSS signals that cannot be reached inside the building can be replaced with Bluetooth and Wifi devices installed in the building. This is very important because activities in buildings are the same as benefits outside the building, such as position interests, spatial patterns, guidance or navigation, etc. for a variety of very broad interests such as smartcity, airports, hospitals, hotels, museums, parking lots, shops, exhibition and others. This research aims to utilize IPS as a means of positioning and guiding inventory objects in building space, which can be developed for various applications. Just as GPS uses satellites for reference positions, IPS also requires a number of iBeacon devices installed at a known position to communicate and determine the location of the receiving device (smartphone). Position information from the device will then be sent to the server and then mapped to the information system. Objects targeted by tracking can already be mapped using IPS based on coordinates obtained from the system, and will then be compiled as an object inventory database. Furthermore, a smartphone is used as a guide to see realtime position and then can track the goods based on coordinates in the inventory database.